TINJAUAN YURIDIS TERHADAP IMPLEMENTASI PIDANA MATI BAGI PELAKU TINDAK PIDANA PEMBUNUHAN BERENCANA - Buulolo, Balasius Basozisekhi (LPPM Universitas Nias Raya, 2025)
The death penalty is the imposition of a crime by depriving an individual who has broken a law that stipulates that their offense is punished by death of their right to life. To get the death penalty is to take someone's life. Severe crimes will carry the death sentence; premeditated murder is one such offense that was tried by a panel of judges at the Sengeti District Court (Decision Number: 36/Pid.B/2013/PN.Snt). In this ruling, the judge determined that the defendant had been shown legally and credibly guilty of premeditated murder. imposed the death punishment on the accused. The study is titled